The 21 May 2014 Mw 5.9 bay of Bengal earthquake : macroseismic data suggest a high-stress-drop event - Martin, Stacey S. (2015)
A modest but noteworthy Mw 5.9 earthquake occurred in the Bay of Bengal beneath the central Bengal fan at 21:51 Indian Standard Time (16:21 UTC) on 21 May 2014. Centered over 300 km from the eastern coastline of India, it caused modest damage by virtue of its location and magnitude. However, shaking was very widely felt in parts of eastern India where earthquakes are uncommon. Media outlets reported as many as four fatalities. Light damage was reported from a number of towns on coastal deltaic sediments, including collapsed walls and damage to pukka and thatched dwellings. Shaking was felt well inland into east‐central India and was perceptible in multistoried buildings as far as Chennai, Delhi, and Jaipur at distances of ≈1600  km. The purpose of this report is to make available the newly collected intensity dataset and to present preliminary analysis of this noteworthy recent earthquake. We further show that the intensity distribution provides evidence for a high-stress drop source. These results bear out the observation made two decades ago by Hanks and Johnston (1992, p. 20): “[Our] results suggest that it should be a fairly simple matter to infer a high-stress-drop event from intensity data alone, provided that an instrumental M0 or Mw value is known separately.” Our study illustrates the potential value of carefully determined intensity data for investigations of earthquake source properties, especially when instrumental recordings are sparse. We suggest it may in fact be a more robust way to estimate stress drop than conventional approaches, which require correction of attenuation to estimate pulse width or corner frequency (e.g., Anderson, 1986); the estimate is then cubed to estimate stress drop (Madariaga, 1976). Lastly, we discuss potentially important implications of our results for efforts to characterize probabilistic seismic hazard in the Himalayan region.